2015
DOI: 10.1002/anie.201503599
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Tandem Transformation with Diynes: Rapid Access to Linear Cyclopentenone‐Fused Polycyclic Molecules

Abstract: An efficient and convenient synthesis of useful linear cyclopentenone-fused polycyclic compounds has been achieved through a novel gold(I)-catalyzed transformation of diynes. The method demonstrates high product yields and tolerates of a wide variety of important functional groups. Gold-vinylidene formation, methoxy group migration, and Nazarov-type cyclization are proposed to be the key steps in the reaction pathway. The synthetic utility of this method is demonstrated by converting the product to eight-membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…On the basis of the above-described results together with the results of previous studies, ,, we suggest that the gold catalyst plays two roles during this cascade reaction. First, its involvement in the HDDA process results in the mechanism switching from a diradical pathway to a cationic pathway.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…On the basis of the above-described results together with the results of previous studies, ,, we suggest that the gold catalyst plays two roles during this cascade reaction. First, its involvement in the HDDA process results in the mechanism switching from a diradical pathway to a cationic pathway.…”
supporting
confidence: 76%
“…Recently, dual gold catalysis has emerged as a powerful tool for de novo synthesis of aromatic rings. Gagosz and our research group independently reported dual gold-catalyzed tetradehydro-Diels–Alder (TDDA) reactions of dienynes to form carbazoles and indolines.…”
mentioning
confidence: 99%
“…Intramolecular transfers of alkoxy groups to gold vinylidene species is also feasible as reported by the Zhang group. 40 When aryl diynes 102 possessing a methoxy group at the propargylic position were reacted with a catalytic amount of [(IPr)Au]NTf 2 in a t-BuOH/DCE mixture at 70 °C, various polyclic fused cylopentenones 106 could be obtained (Scheme 25). To explain their formation, the authors proposed that a transfer of the methoxy group from the allylic position to the gold vinylidene moiety could proceed in the intermediately formed species 103.…”
Section: Scheme 24 Reaction Of Gold Vinylidene Species With Watermentioning
confidence: 99%
“…In several early studies, gold vinylidenes were proposed as reactive intermediates that underwent facile C–H or Nu–H insertion [Equation (1)]. Only a few reports appeared in which a gold vinylidene was trapped with one nucleophile such as water or a methoxy group [Equation (2)]. In line with our interests in exploring new reactivities of Au vinylidenes, we continue to be inspired by other metal vinylidene complexes such as Ru, Rh, and W .…”
Section: Introductionmentioning
confidence: 98%